Chlamydia abortus Pmp18.1 Induces IL-1β Secretion by TLR4 Activation through the MyD88, NF-κB, and Caspase-1 Signaling Pathways - Pan, Qing; Zhang, Qiang; Chu, Jun; Pais, Roshan; Liu, Shanshan; He, Cheng; Eko, Francis O. (Frontiers in Cellular and Infection Microbiology, 2017)
The polymorphic membrane protein D (Pmp18D) is a 160-kDa outer membrane protein that is conserved and plays an important role in C. abortus pathogenesis. We have identified an N-terminal fragment of Pmp18D (designated Pmp18.1) as a possible subunit vaccine antigen. In this study, we evaluated the vaccine potential of Pmp18.1 by investigating its ability to induce innate immune responses in dendritic cells and the signaling pathway(s) involved in rPmp18.1-induced IL-1β secretion. We next investigated the immunomodulatory impact of VCG, in comparison with the more established Th1-promoting adjuvants, CpG and FL, on rPmp18.1-mediated innate immune activation. Finally, the effect of siRNA targeting TLR4, MyD88, NF-κB p50 and Caspase-1 mRNA in DCs on IL-1β cytokine secretion was also investigated. Bone marrow-derived dendritic cells (BMDCs) were stimulated with rPmp18.1 in the presence or absence of VCG or CpG or FL and the magnitude of cytokines produced was assessed using a multiplex cytokine ELISA assay. Expression of costimulatory molecules and Toll-like receptors (TLRs) was analyzed by flow cytometry. Quantitation of intracellular levels of myeloid differentiation factor 88 (MyD88), nuclear factor kappa beta (NF-κB p50/p65) and Caspase-1 was evaluated by Western immunoblotting analysis while NF-κB p65 nuclear translocation was assessed by confocal microscopy. The results showed DC stimulation with rPmp18.1 provoked the secretion of proinflammatory cytokines and upregulated expression of TLRs and co-stimulatory molecules associated with DC maturation. These responses were significantly (p< 0.001) enhanced by VCG but not CpG or FL. In addition, rPmp18.1 activated the expression of MyD88, NF-κB p50 and Caspase-1 as well as the nuclear expression of NF-κB p65 in treated DCs. Furthermore, targeting TLR4, MyD88, NF-κB p50 and Caspase-1 mRNA in BMDCs with siRNA significantly reduced their expression levels, resulting in decreased IL-1β cytokine secretion, strongly suggesting their involvement in the rPmp18.1-induced IL-1β cytokine secretion. Taken together, these results indicate that C. abortus Pmp18.1 induces IL-1β secretion by TLR4 activation through the MyD88, NF-κB as well as the Caspase-1 signaling pathways and may be a potential Chlamydia abortus vaccine candidate. The vaccine potential of Pmp18.1 will subsequently be evaluated in an appropriate animal model, using VCG as an immunomodulator.